Double-template molecularly imprinted electrochemical sensor based on black phosphorus-gold / silver nano composite material as well as preparation method and application of double-template molecularly imprinted electrochemical sensor
By using dual-template molecularly imprinted modified electrodes of black phosphorus-gold/silver nanocomposite in the electrochemical sensor, the problem of simultaneous detection of fleroxacin and vancomycin with existing technology is solved, achieving highly sensitive and selective detection. Effect.
Patent Information
- Application Number
- CN202411306123.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-19
Smart Images

Figure CN119355071A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical sensors, and in particular to a double-template molecular imprinting electrochemical sensor of a black phosphorus-gold / silver nanocomposite material and a preparation method and application thereof. Background Art
[0002] Fleroxacin (FLE), as a quinolone antibiotic, is widely used to treat respiratory, urinary, and biliary tract infections caused by Gram-negative bacteria and Chlamydia. However, the abuse of FLE may bring serious health risks, including gastrointestinal dysfunction, central nervous system damage, and allergic reactions when overdose. On the other hand, vancomycin (VA), as a representative of glycopeptide antibiotics, is an important drug for the treatment of severe Gram-positive bacterial infections, but its high-dose use is potentially toxic to the ears and kidneys, and low doses may also induce hypersensitivity reactions. It is worth noting that the simultaneous or unreasonable combination of FLE and VA may aggravate the toxic effects and produce superimposed negative effects.
[0003] In view of the urgent need for food safety and environmental protection, it is particularly important to monitor the residues of FLE and VA in matrices such as animal-derived foods and the natural environment. Currently, although the detection technologies for these two antibiotics, such as immunoassay, capillary electrophoresis and high-performance liquid chromatography, show high sensitivity and accuracy, they are limited by high equipment costs, complex operating procedures and long analysis cycles, which restricts their application in a wide range of fields.
[0004] In this context, electrochemical sensing technology has gradually become the mainstream means of detecting antibiotic residues in the environment due to its advantages such as rapid response, simple preparation and high sensitivity. In order to improve the performance of electrochemical sensors, researchers often use materials such as carbon-based nanomaterials, precious metals, transition metal compounds and conductive polymers to carefully modify electrodes to enhance their detection capabilities. However, the selectivity challenges faced by traditional electrochemical sensors cannot be ignored, especially the signal interference that may be caused by complex matrices in real samples.
[0005] To overcome this problem, molecularly imprinted polymers (MIPs) electrochemical sensors came into being, which cleverly combined the high selectivity of molecular imprinting technology with the high efficiency of electrochemical sensing. MIPs electrochemical sensors generate response signals through two main mechanisms: directly measuring the redox current induced by the target molecules bound to the imprinted sites (applicable to electrochemically active substances such as FLE), or using the "gate effect" principle to detect non-electrochemically active substances (such as VA) through the signal changes caused by the probe molecules entering the imprinted cavity, thereby achieving compatible detection of a wide range of analytes.
[0006] In view of the electrochemical activity of FLE and the non-electrochemical properties of VA, traditional MIPs electrochemical sensors still cannot meet the detection needs of both at the same time. Therefore, it is of great significance to develop a new MIPs electrochemical sensor for the detection of FLE and VA. Summary of the invention
[0007] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a dual-template molecular imprinting electrode of black phosphorus-gold / silver nanocomposite material, which can be used for simultaneous detection of FLE and VA.
[0008] The invention also provides a method for preparing the electrode.
[0009] The present invention also provides a sensor with the above-mentioned electrode.
[0010] The invention also provides a method for preparing the sensor.
[0011] The present invention also provides an application of the sensor.
[0012] According to the first aspect of the present invention, a dual-template molecular imprinting modified electrode of a black phosphorus-gold / silver nanocomposite material is implemented, the modified electrode comprises an electrode substrate, the electrode substrate is sequentially modified with an electrode sensitizing material layer and a dual-template molecular imprinting polymer film layer, an electrochemical probe is combined in the dual-template molecular imprinting polymer film layer, wherein the electrode sensitizing material layer comprises a black phosphorus nanoparticle-gold / silver nanoparticle composite material (BPNS-Au / AgNPs), and the template of the dual-template molecular imprinting polymer film layer is fleroxacin (FLE) and vancomycin (VA).
[0013] The modified electrode according to the embodiment of the present invention has at least the following beneficial effects: the scheme of the present invention cleverly designs a modified electrode with an integrated dual-signal response mechanism, which can achieve efficient detection of FLE and VA simultaneously through only one interface. This breakthrough design cleverly utilizes the dual-template molecular imprinting technology to embed specific recognition sites in the polypyrrole film layer. When the template molecules are removed, the remaining holes serve as channels for electrochemical probes to enter and attach to the surface of the BPNS-Au / AgNPs composite substrate, greatly promoting the electron transfer efficiency and sensing performance.
[0014] As a reinforcing material for the electrode substrate, BPNS-Au / AgNPs not only enhances the electron conduction ability with its unique nanostructure, but also effectively anchors the target analytes through its excellent catalytic activity and large specific surface area, thereby significantly improving the detection sensitivity of the sensor. The synergistic enhancement mechanism between BPNS-Au / AgNPs and the dual-template molecular imprinting membrane enables the sensor to show excellent sensitivity, selectivity and stability in the detection of FLE and VA in a wide concentration range (0.001μM to 10μM).
[0015] Specifically, for FLE, the sensor exhibited two linear detection ranges: low concentration (1nM to 1μM) and high concentration (1μM to 10μM), with a detection limit (LOD) as low as 0.25nM, fully demonstrating its high sensitivity. For VA, the sensor exhibited good linear response in the entire detection range (0.001μM to 10μM), and the LOD reached 0.17nM, further highlighting its excellent detection performance.
[0016] In addition, the modified electrode (MIP / BPNS-Au / AgNP / GCE) also performed well in practical applications and was able to accurately detect FLE and VA in sewage and milk samples, with recoveries ranging from 91.17% to 107.97% and 91.91% to 104.83%, respectively, fully verifying its practicality and reliability in actual environmental monitoring and food safety testing.
[0017] In summary, the dual-template molecular imprinting electrochemical sensing platform of the present invention, with its rapid response, simple operation, high cost-effectiveness and excellent detection performance, shows broad application prospects in the fields of environmental monitoring, food safety analysis, etc., and opens up a new direction for the development of electrochemical sensing technology.
[0018] According to some embodiments of the present invention, the electrochemical probe contains methylene blue, ferrocene or [Fe(CN)6] 3- / 4- According to some embodiments of the present invention, the electrode substrate is at least one of a glassy carbon electrode (GCE), a screen printed carbon electrode (SPCE) or a gold electrode.
[0019] According to some embodiments of the present invention, the polymer film layer is at least one of a polypyrrole film layer, a polyaniline film layer, a polythiophene film layer, a polydopamine film layer, and a poly-o-phenylenediamine film layer.
[0020] The method for preparing a modified electrode according to the second aspect of the present invention comprises the following steps:
[0021] S1. Preparing a black phosphorus nanoparticle-gold / silver nanoparticle composite material: mixing chloroauric acid and black phosphorus, reacting them under ultraviolet light, collecting a solid phase part I by solid-liquid separation, preparing the solid phase part I into a dispersion liquid I, adding a silver salt, dispersing the silver salt in the dispersion liquid I, reacting them again under ultraviolet light, and collecting a solid phase part II by solid-liquid separation again, thereby obtaining a black phosphorus nanoparticle-gold / silver nanoparticle composite material;
[0022] S2, preparing the black phosphorus nanoparticle-gold / silver nanoparticle composite material into a dispersion II, so that the dispersion forms an electrode sensitization material layer on the electrode substrate;
[0023] S3, forming a double-template molecular imprinting polymer film layer by electropolymerizing the functional monomers and the template molecules on the surface of the electrode sensitizing material layer;
[0024] S4, eluting and removing the template, placing in an electrochemical probe solution so that the surface of the dual-template molecularly imprinted polymer film layer is bound to the electrochemical probe, thereby obtaining the modified electrode;
[0025] Wherein, the template molecule is a mixture of fleroxacin and vancomycin.
[0026] According to the preparation method of the embodiment of the present invention, at least the following beneficial effects are achieved: the preparation method of the scheme of the present invention is easy to operate and has good application prospects. The scheme of the present invention utilizes effective irradiation of ultraviolet light to promote the generation of significantly increased active electron-hole pairs inside black phosphorus nanoparticles (BPNS). This process not only enriches the surface free electron density of black phosphorus nanoparticles (BPNS), significantly enhances its reducing ability, but also gives BP the dual role of a noble metal photocatalyst and an ideal matrix. The ingenuity of the present invention lies in that, through ultraviolet-assisted fine regulation, BP self-optimization and the composite of noble metal nanoparticles (such as gold nanoparticles AuNPs and silver nanoparticles AgNPs) are achieved to form a BPNS-Au / AgNPs bimetallic nanocomposite material. The composite material, by virtue of its increased specific surface area, provides abundant active sites for efficiently anchoring target molecules, thereby greatly improving the sensitivity of the detection system.
[0027] Furthermore, the present invention innovatively introduces BPNS-Au / AgNPs as electrode sensitization materials into the field of electrochemical sensing, selects pyrrole as the functional monomer, and accurately constructs a dual-template molecular imprinting membrane on the surface of BPNS-Au / AgNPs modified glassy carbon electrode (GCE) through electropolymerization technology. This membrane structure can specifically identify and capture target analytes, such as FLE and VA, and at the same time, combined with highly sensitive electrochemical probe technology, it achieves highly selective and highly sensitive detection of these two compounds. This solution not only broadens the application scope of black phosphorus nanomaterials in electrochemical sensing, but also provides new ideas and technical means for the rapid and accurate detection of small molecules in complex biological systems.
[0028] According to some embodiments of the present invention, in step S1, the molar ratio of chloroauric acid to silver salt is 0.5 to 2:1, such as 1:1.
[0029] According to some embodiments of the present invention, in step S1, the molar ratio of black phosphorus to chloroauric acid is 10:15-25.
[0030] According to some embodiments of the present invention, in step S1, the conditions for the reaction under ultraviolet light irradiation include at least one of the following conditions: 1) the wavelength of the ultraviolet light is 360-370nm; 2) the reaction time is 50-70min; 3) the ultraviolet light is emitted by an ultraviolet lamp, and the power of the ultraviolet lamp is 45-55W.
[0031] According to some embodiments of the present invention, in step S1, the conditions for the reaction under ultraviolet light irradiation include at least one of the following conditions: 1) the wavelength of the ultraviolet light is 365nm; 2) the reaction time is 60min; 3) the ultraviolet light is emitted by an ultraviolet lamp, and the power of the ultraviolet lamp is 50W.
[0032] According to some embodiments of the present invention, in step S1, the conditions for the reaction under ultraviolet light irradiation again include at least one of the following conditions: 1) the wavelength of the ultraviolet light is 360-370nm; 2) the time is 80-100min; 3) the ultraviolet light is emitted by an ultraviolet lamp, and the power of the ultraviolet lamp is 45-55W.
[0033] According to some embodiments of the present invention, in step S1, the conditions for the reaction under ultraviolet light irradiation again include at least one of the following conditions: 1) the wavelength of the ultraviolet light is 365nm; 2) the time is 90min; 3) the ultraviolet light is emitted by an ultraviolet lamp, and the power of the ultraviolet lamp is 50W.
[0034] According to some embodiments of the present invention, the molar ratio of the functional monomer, fleroxacin and vancomycin in step S3 is 0.25-4:1:1.
[0035] According to some embodiments of the present invention, the functional monomer is at least one of pyrrole, aniline, thiophene, dopamine, and o-phenylenediamine.
[0036] According to some embodiments of the present invention, the number of electropolymerization cycles is 5 to 15 cycles, preferably 10 cycles.
[0037] According to some embodiments of the present invention, the template is eluted by electrochemical elution; specifically, the number of CV cycles in the process of eluting the dual templates by CV scanning is more than 60 cycles, preferably 60 cycles, which can achieve stability and thus save energy.
[0038] According to some embodiments of the present invention, in step S4, the electrochemical probe is bound to the surface of the dual-template molecularly imprinted polymer membrane layer by cyclic voltammetry scanning.
[0039] According to some embodiments of the present invention, the cyclic voltammetry scan is performed to make the redox peak current in the cyclic voltammetry curve change by less than 2%.
[0040] According to some embodiments of the present invention, the electrochemical probe solution is 2-3 mmol / L [Fe(CN)6] 3- / 4- Solution.
[0041] According to the sensor of the third aspect of the present invention, the sensor includes an electrode system and a supporting electrolyte solution.
[0042] According to some embodiments of the present invention, the sensor further comprises a reference electrode and an auxiliary electrode.
[0043] According to some embodiments of the present invention, the reference electrode is a saturated calomel electrode or an Ag / AgCl electrode.
[0044] According to some embodiments of the present invention, the auxiliary electrode is a platinum wire.
[0045] The preparation method according to the fourth aspect of the present invention comprises the step of preparing the modified electrode by the above-mentioned preparation method of the modified electrode.
[0046] According to some embodiments of the present invention, the preparation method further comprises the step of combining an auxiliary electrode, a reference electrode and a supporting electrolyte solution to form a sensor.
[0047] According to some embodiments of the invention, the supporting electrolyte comprises phosphate buffered salt.
[0048] According to some embodiments of the present invention, the concentration of the phosphate buffer in the supporting electrolyte solution is 0.08-0.12 mol / L, such as 0.1 mol / L.
[0049] According to some embodiments of the present invention, the pH of the supporting electrolyte solution is 4 to 7, such as 4, 5, 6 or 7.
[0050] According to the application of the fifth aspect of the present invention, the above-mentioned sensor is used in detecting FLE and / or VA.
[0051] The application of the fifth embodiment of the present invention also includes a method for detecting antibiotics using the above sensor, comprising the following steps: placing the modified electrode in a solution containing a supporting electrolyte and antibiotics, and incubating the modified electrode in a solution containing a supporting electrolyte and antibiotics, using a dual signal strategy to detect [Fe(CN)6] 3- / 4- The electrochemical probe is used to detect the antibiotics by voltammetry; wherein the antibiotics include fleroxacin (FLE) and / or vancomycin (VA), and the voltammetry is one of linear sweep voltammetry (LSV), differential pulse voltammetry (DPV), and square wave pulse voltammetry (SWV).
[0052] According to some embodiments of the present invention, the incubation time is 6 to 10 minutes.
[0053] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:
[0055] Figure 1 Schematic diagram of the preparation route of the modified electrode in the embodiment of the present invention;
[0056] Figure 2 The characterization results of the raw materials, intermediate products and finished products of the modified electrode in the embodiments of the present invention are as follows: TEM images of BPNS (A) and BPNS-Au / AgNP (B); HAADF-STEM image of BPNS-Au / AgNP (CF); XRD spectra (G), Raman spectra (H) and XPS spectra (I) of BPNS and BPNS-Au / AgNP.
[0057] Figure 3 These are AFM images of the modified electrodes prepared in the examples of the present invention and the comparative examples before and after elution: AFM images of MIP / BPNS-Au / AgNP / GCE before elution (A), after elution (B) and AFM images of NIP / BPNS-Au / AgNP / GCE before elution (C), after elution (D).
[0058] Figure 4The results of parameter optimization test in the preparation and application of modified electrodes according to the present invention are shown in Figure 1: The optimization of analytical parameters, the loading amount of BPNS-Au / AgNPs (A), the number of electropolymerization cycles (B), the molar ratio of VA:FLE:Py (C), the elution cycle (D), and the incubation time (E) on the i of FLE and VA pa The i of 10 μM VA was recorded at different pH values of PBS buffer (0.1 M). pa The relationship between pH value (F); LSV curve of 10 μM FLE (G) and i pa or E pa Relationship graph with pH value (H).
[0059] Figure 5 The modified electrodes of the embodiments of the present invention and the comparative examples contain 5 mM [Fe(CN)6] 3- / 4- Cyclic voltammetry curves (A, B) and Nyquist plots (C, D) of different electrodes in 0.1 M KCl.
[0060] Figure 6 It is the peak current corresponding to 10 μM FLE and VA measured on different electrodes in the test example of the present invention.
[0061] Figure 7 The CV curves (A) and (B) of 10 μM FLE obtained by using MIP / BPNS-Au / AgNP / GCE at different scan rates (v) in the test example of the present invention are as follows: pa and v(B), log(i pa ) and log(v)(C), E pa Linear relationship diagram between lnv (D) and electrochemical mechanism of FLE oxidation on MIP / BPNS-Au / AgNP / GCE (E).
[0062] Figure 8 The figures are the LSV curves (A) of the MIP / BPNS-Au / AgNP / GCE prepared in the embodiment of the present invention after incubation in different concentrations of VA (0.001-10 μM) and the linear relationship diagram between the anodic peak current and the concentration in the range of 0.001-10 μM (B), the LSV curves (C) of the MIP / BPNS-Au / AgNP / GCE after incubation in different concentrations of FLE (0.001-10 μM) and the calibration curves of the change of FLE concentration with potassium ferrocyanide current (D) and the change of FLE peak current (E).
[0063] Fig. 9It is the peak current (A) corresponding to the LSV after the MIP / BPNS-Au / AgNP / GCE prepared in the embodiment of the present invention was incubated with 1 μM dual template and environmental interferents, and the LSV peak current (B) after incubation with the interferents of the same concentration as the target analyte (1:1).
[0064] Fig.10 It is a bar graph of the test example of the present invention measuring 1 μM target analyte seven times in the same MIP / BPNS-Au / AgNP / GCE (A), the 1 μM target analyte response peak current recorded at five independent MIP / BPNS-Au / AgNP / GCE (B), and the target analyte response peak current within 28 days (C).
[0065] Fig.11 It is a linear relationship diagram of MIP / BPNS-Au / AgNP / GCE prepared in an embodiment of the present invention after incubation in sewage (A) and milk (B) with the addition of different concentrations of FLE (0.1-1 μM); it is a linear relationship diagram of MIP / BPNS-Au / AgNP / GCE after incubation in sewage (C) and milk (D) with the addition of different concentrations of VA (0.1-1 μM). DETAILED DESCRIPTION
[0066] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0067] In the description of the present invention, it should be understood that if I and II are described, they are only used to distinguish the technical features, and cannot be understood as indicating or implying the relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0068] In the description of the present invention, the description with reference to the terms "one embodiment", "some implementations", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0069] The purity and manufacturer information of some reagents used in the following embodiments, comparative examples and test examples are shown in Table 1 below:
[0070] Table 1
[0071]
[0072]
[0073] The model specifications and manufacturer information of the instruments used in the following test examples are shown in Table 2:
[0074] Table 2
[0075]
[0076] Example
[0077] In this example, a dual-template molecular imprinting modified electrode (MIP / BPNS-Au / AgNP / GCE) based on black phosphorus-gold / silver nanocomposite material was prepared. The modified electrode included an electrode substrate, which was sequentially modified with an electrode sensitizing material layer and a dual-template molecular imprinting polymer film layer, and an electrochemical probe was combined in the dual-template molecular imprinting polymer film layer, wherein the electrode sensitizing material layer was made of a BPNS-Au / AgNPs composite material, and the template of the dual-template molecular imprinting polymer film layer was FLE and VA.
[0078] Its preparation route is Figure 1 The specific preparation process is as follows:
[0079] 1) Preparation of BPNS-Au / AgNPs: 1 mL HAuCl4·4H2O (10 mM) was dispersed in 2 mL black phosphorus crystals (300 μg / mL, 100-500 μg / mL) and ultrasonicated for 10 min. The mixed solution was irradiated with a UV lamp (365 nm, 50 W) for 1.0 h. The precipitate was obtained by centrifugation at 10,000 r / min for 6 min. The obtained precipitate was dispersed in 2 mL DIW (deionized water) to obtain a BPNS-AuNPs dispersion. Subsequently, 1 mL AgNO3 (10 mM) solution was dispersed in 2 mL BPNS-AuNPs, ultrasonicated for 10 min, and irradiated with a UV lamp (365 nm, 50 W) for 1.5 h. The precipitate was obtained by centrifugation at 10,000 r / min for 6 min, and the obtained precipitate was dispersed in 1 mL DIW again and stored in a refrigerator at 4°C for later use.
[0080] 2) Preparation of MIP / BPNS-Au / AgNP / GCE: Before electrode modification, the glassy carbon electrode (GCE, diameter 3.0 mm) was pretreated (the glassy carbon electrode was ground and polished with 0.5, 0.3, and 0.05 μm Al2O3 powder on suede, and then ultrasonically cleaned with ultrapure water, anhydrous ethanol, and ultrapure water, and dried with nitrogen (infrared lamp radiation drying or natural drying can also be used)). First, 4 μL of BPNS-Au / AgNPs was drop-coated on the surface of GCE, and BPNS-Au / AgNP / GCE was obtained after drying. Subsequently, in an aqueous solution containing 10 mM VA, 10 mM FLE, and 10 mM Py (VA: FLE: PY = 1:1:1), the potential range of 0-1.5 V was 100 mV s -1 15 cycles of CV scans were performed at a scan rate of 100 mV s to achieve electropolymerization of PPy. Then, the template was removed by electrochemical elution. That is, continuous CV scans (potential range: -1.0-+1.0 V; scan rate: 100 mV s) were applied to the obtained electrode in 0.1 M NaOH. -1 ) until the probe solution (2.5 mM [Fe(CN)6] 3- / 4- ) showed an obvious and stable redox peak (the redox peak current change was less than 2%), and MIP / BPNS-Au / AgNP / GCE was obtained.
[0081] The modified electrode, saturated calomel electrode and platinum wire were constructed into an electrode system, and an electrochemical sensor was constructed with 0.1 M PBS solution (pH=5) as a supporting electrolyte.
[0082] The operation process of the above sensor for detecting antibiotics is as follows:
[0083] The modified electrode was placed in a solution containing supporting electrolyte and antibiotics and incubated using a dual signal strategy with [Fe(CN)6] 3- / 4- It is an electrochemical probe, and the antibiotics are detected by voltammetry; wherein the antibiotics include FLE and / or VA, and the voltammetry can be any one of LSV, DPV, and SWV. In this embodiment, LSV is specifically used.
[0084] Comparative Example
[0085] In this example, a modified electrode (NIP / BPNS-Au / AgNP / GCE) based on black phosphorus-gold-silver nanocomposite non-molecular imprinting polymer was prepared, which differed from the embodiment only in that no template molecule was added during electropolymerization.
[0086] The modified electrode was constructed into a sensor based on the same method as in the examples.
[0087] Test Case
[0088] In this example, the performance of the electrodes prepared in the embodiments and test examples is characterized and tested.
[0089] 1) Morphological characterization
[0090] The structure and morphology of black phosphorus crystals and BPNS-Au / AgNPs composites were characterized by TEM, EDS, XRD, XPS, and Raman spectroscopy. Figure 2 shown.
[0091] from Figure 2 It can be seen that the black phosphorus crystals have a typical layered structure and a smooth surface with a diameter of about 200nm. TEM of BPNS-Au / AgNPs shows that spherical Au / AgNPs with a particle size of about 50nm are uniformly loaded on the layered BPNS surface ( Figure 2 B). Elemental mapping of BPNS-Au / AgNPs ( Figure 2 CF) Ag, Au, P, and O elements are uniformly distributed. XRD patterns of BPNS and BPNS-Au / AgNPs are shown in Figure 2. Figure 2 G. BPNS exhibits three characteristic diffraction peaks at 16.9°, 34.2° and 52.3°, which are respectively attributed to the (020), (040) and (060) crystal planes of orthorhombic BP (JCPDS#73-1358). In addition to the three characteristic diffraction peaks of BP, BPNS-Au@AgNPs also exhibits four additional diffraction peaks at 38.2°, 44.3°, 64.7° and 77.5°, which are respectively attributed to the (111), (200), (220) and (311) crystal planes of Au@AgNPs, confirming that Au / AgNPs are successfully anchored on the surface of BPNS. Figure 2 H is the Raman spectra of BP crystal, BPNS and BPNS-Au@AgNP. BP crystal has the Raman spectra at 361, 437 and 465 cm -1 Obvious characteristic peaks appear, corresponding to the in-plane vibration mode A 1g and out-of-plane vibration modes B2g and A 2g Compared with BP crystal, the three characteristic peaks of BPNS are slightly red-shifted by about 2 cm -1 . Studies have shown that BP exhibits obvious anisotropic electron-phonon interactions, and its Raman characteristic peak position is closely related to polarization, wavelength and thickness. Therefore, the red shift of the characteristic Raman peak of BPNS indicates that the BP crystal is successfully exfoliated into a few layers of BPNS. Figure 2 I is the XPS spectra of BPNS and BPNS-Au@AgNP. In the P 2p fine spectrum of BPNS, 2p 3 / 2 and 2p 1 / 2In addition, an obvious broad peak was observed at 133.8 eV, which may be derived from the P generated on the surface of BPNSs. x O y This indicates that BP was slightly oxidized during the stripping process. BPNS-Au@AgNP exhibits two sharp peaks at 87.03 and 83.33 eV, which are attributed to the 0-valent Au 4f 5 / 2 and 4f 7 / 2 ; The Ag 3d fine spectrum also shows two sharp peaks at 373.51 and 367.51 eV, which is mainly related to the Ag 0 3D 3 / 2 and 3D 5 / 2 Related. At the same time P 2p 1 / 2 and 2p 3 / 2 The peak of BP is slightly red-shifted (about 0.2 eV), which may be due to the electron transition from BP with a higher Fermi level to the noble metal NPs. The underlying mechanism may be due to the redox reaction between BP and noble metal ions. The work function of BP is related to the thickness, and the Fermi level of BP is much higher than that of AuCl4 - and Ag + Therefore, BP / AuCl4 - BP / Ag + A redox pair can be formed, and electrons are spontaneously transferred from BP to AuCl4 - and Ag + , thereby generating AuNPs and AgNPs. It is worth noting that P x O y The intensity of the characteristic peaks decreased significantly compared with that of BPNS, indicating that Au / AgNPs significantly improved the stability of BPNS. In summary, BPNS-Au / AgNPs contain Au 4f, Ag 3d, and P 2p characteristic peaks, indicating that Au and Ag exist simultaneously on the BP matrix.
[0092] AFM was used to analyze the morphology of MIPs and NIPs before and after template removal. Figure 3 As shown in A, in the presence of dual template molecules, the roughness of the MIPs film is relatively large (Ra = 23.1nm); in the absence of dual template molecules, a relatively dense and less rough film is formed on the NIPs surface, and the average surface roughness Ra is 16.7nm ( Figure 3 C) Figure 3 As shown in Figure B, after eluting FLE and VA from MIP, the roughness of MIPs increased (average roughness Ra = 46.1 nm), indicating that imprinted cavities were formed in the MIP membrane. For NIP, after “template removal”, the roughness of the NIP membrane remained almost unchanged (Ra = 21.0 nm, Figure 3 D).
[0093] 2) Parameter optimization analysis during the preparation process
[0094] 2.1 BPNS-Au / AgNPs loading
[0095] Figure 4 A is the effect of BPNS-Au / AgNPs loading on the anodic oxidation peak current of FLE (i pa As the BPNS-Au / AgNPs loading amount increased from 2 μL to 4 μL, the electrode surface was continuously covered by BPNS-Au / AgNPs, so i pa (FLE) also increases accordingly. However, when the BPNS-Au / AgNPs loading exceeds 4 μL, the sensing layer BPNS-Au / AgNPs is too thick, which seriously hinders the electron transfer. pa Therefore, the optimal loading amount of BPNS-Au / AgNPs is 4 μL.
[0096] 2.2 Number of electropolymerization cycles
[0097] The number of electropolymerization cycles is an important parameter in the electropolymerization process, which is directly related to the thickness of the MIP film. Therefore, the thickness of the MIP film can be regulated by the number of electropolymerization cycles. Figure 4 As shown in B, i pa (FLE) and Δi pa ([Fe(CN)6] 3- ) reached the maximum value after 10 cycles of electropolymerization; more than 10 cycles, i pa (FLE) and Δi pa ([Fe(CN)6] 3- ) drops sharply. As the number of electropolymerization cycles increases, the thickness of the MIP film increases, and the number of imprinted cavities that can be carried also increases. pa (FLE) and Δi([Fe(CN)6] 3- ) are constantly increasing. Too many electropolymerization cycles will lead to too thick MIP film, thereby increasing the electron transfer resistance and causing i pa (FLE) and Δi pa ([Fe(CN)6] 3- ) decreased. Therefore, the optimal number of electropolymerization cycles is 10.
[0098] 2.3 Template:monomer ratio
[0099] The strength of template-MIP binding is highly related to the ratio of the two templates to the functional monomers. Figure 4 C is the difference between VA:FLE:Py and i pa (FLE) and Δi pa ([Fe(CN)6] 3-). VA:FLE:Py is in the range of 1:1:0.25 to 1:1:4, i pa (FLE) and Δi([Fe(CN)6] 3- ) both reach their maximum at 1:1:1. When the concentration of the functional monomer is low, the MIP membrane is thinner, the number of imprinted cavities carried is very limited, and the adsorption capacity of the imprinted cavities to the template is not strong; however, a high concentration of Py will cause the MIP to be too thick, the conductivity of the MIP membrane will deteriorate, and the template embedded in the MIP will be difficult to completely remove, so the specific recognition ability of the MIP to the template will decrease. Therefore, the optimal molar ratio of VA:FLE:Py is 1:1:1.
[0100] 2.4 Template elution
[0101] After MIP electropolymerization, the template is embedded in the molecular imprinting cavity. This chapter adopts the electrochemical elution strategy to elute the dual templates by CV scanning. Obviously, the number of CV scanning cycles will directly affect the effect of template removal. After template elution, the [Fe(CN)6] 3- / 4- The diffusion and subsequent redox of pa ([Fe(CN)6] 3- ) changes (Δi pa ([Fe(CN)6] 3- )) can be used to evaluate the template removal efficiency. Figure 4 As shown in D, as the number of CV scans increases from 30 to 60, Δi(Fe(III)) increases continuously. pa ([Fe(CN)6] 3- ) tends to be stable, indicating that the template is completely removed or the template removal has reached its limit. Therefore, the optimal CV scanning cycle for electrochemical elution of template is 60.
[0102] 2.5 Incubation time
[0103] like Figure 4 As shown in E, as the incubation time increases, the i pa (FLE) gradually increased, reaching a maximum at 7 minutes, and then tended to saturation. This indicates that the imprinted cavity in the MIP membrane gradually combined with the template, and the combination of the template and the imprinted cavity reached saturation after 7 minutes. Therefore, the optimal incubation time was set to 7 minutes.
[0104] 2.6 pH of supporting electrolyte solution
[0105] Figure 4 F is the corresponding Δi at different supporting electrolyte solution pH (2.0-8.0) pa ([Fe(CN)6] 3-) and pH, it can be seen that as the buffer pH increases from 2.0 to 5.0, Δi([Fe(CN)6] 3- ) gradually increased and reached the maximum at pH 5.0. Figure 4 G is the LSV curve of FLE at different buffer pH (2.0-8.0), and the corresponding i pa The relationship between (FLE) and pH is as follows Figure 4 As the pH increases, the anodic peak potential of FLE shifts negatively, indicating that protons (H + ) participates in FLE oxidation. As the pH of the supporting electrolyte solution increases from 2.0 to 5.0, i pa (FLE) gradually increases and reaches its maximum at pH 5.0; as pH continues to increase, i pa (FLE) drops sharply. Therefore, with the optimal supporting electrolyte solution pH set to 5.0. pa ) has a good linear correlation with the pH of the buffer solution, and the linear regression equation is E pa (V) = -0.06715pH + 1.377 (R 2 =0.9995)( Figure 4 G). The slope (-67.15mV pH -1 ) is close to the Nernst theoretical value (-59.2mV pH -1 ), indicating that FLE oxidation involves isoelectronic and isoproton transfer.
[0106] 3) Electrochemical performance test
[0107] In 2.5 mM [Fe(CN)6] 3- / 4- CV and electrochemical impedance spectroscopy (EIS) of different electrodes were recorded in redox probe solution to characterize their electrochemical performance. LSV was used to quantitatively detect FLE and VA. The specific test method was as follows: MIP / BPNS-Au / AgNP / GCE was placed in a mixed solution of VA and FLE (VA:FLE=1:1) with different concentrations and incubated for 7 min under stirring. Then, MIP / BPNS-Au / AgNP / GCE was transferred to 2.5 mM [Fe(CN)6] 3- / 4- In the case of 100mV s -1 The LSV curves from -0.2 to 1.4 V were recorded at a scan rate of .
[0108] 3.1[Fe(CN)6] 3- / 4- Electrochemical behavior on modified electrodes
[0109] In 5 mM [Fe(CN)6] 3- / 4-and 0.1 M KCl solution, the stepwise construction process of BPNS-Au / AgNP / GCE was investigated by CV (e.g. Figure 5 A). The bare GCE observed [Fe(CN)6] 3- / 4- A pair of symmetrical redox peaks, i pa and i pc When BPNSs modified GCE, i pa and i pc The results show that the BPNS-Au / AgNPs can improve the electron transfer of GCE. pa and i pc There was a significant increase (i pa =204μA; i pc =-184.1 μA), which may be due to the fact that Au / AgNPs improved the stability of black phosphorus and the synergistic effect of BPNS and Au / AgNPs enhanced the catalytic activity.
[0110] Due to the electron transfer blocking of PPy matrix, [Fe(CN)6] 3- / 4- The redox peaks on MIP / BPNS-Au / AgNP / GCE almost disappeared (e.g. Figure 5 B). After the template is eluted, a pair of sharp redox peaks appear (i pa =126.5μA; i pc =-117.1μA), because the imprinted cavity promotes [Fe(CN)6] 3- / 4- The diffusion and redox of [Fe(CN)6] 3- / 4- i pa and i pc Significantly reduced (i pa =100.1μA; i pc =-103.5μA), which may be due to the binding of FLE and VA to the imprinted cavity, inhibiting the [Fe(CN)6] 3- / 4- In addition, the voltammetric response of MIP / BPNS-Au / AgNP / GCE is much higher than that of MIP / GCE (i pa =89.43μA; i pc =-82.71 μA), indicating that BPNS-Au / AgNP with a large surface area can carry more imprinting sites. In contrast, due to the lack of effective imprinting sites, no obvious redox peaks appeared on NIP / BPNS-Au / AgNP / GCE.
[0111] Figure 5 C and D show the Nyquist curves of different electrodes at open circuit voltage. When BPNS-Au / AgNPs modified GCE, its R ct When the imprinted PPy film was coated on BPNS-Au / AgNP, R ct This is mainly due to the poor conductivity of the MIP film, which hinders the transfer of electrons from the solution to the electrode. After removing the template, the R ct decreased, indicating that the template molecules have been effectively removed from the MIP membrane and the imprinted holes enhance the porosity of the MIP, thereby promoting the [Fe(CN)6] 3- / 4- In contrast, NIP / BPNS-Au / AgNP / GCE shows the largest semicircle compared to its MIP counterpart, which is due to the considerable electron transport barrier of the compact and non-conductive NIP film. The results are consistent with the CV current response trend.
[0112] 3.2 Electrochemical responses of FLE and VA on different modified electrodes
[0113] LSV was used to record the relationship between FLE and [Fe(CN)6] 3- / 4- The changes of anode peak current at different electrodes were used to evaluate the detection performance of FLE and VA (e.g. Figure 6 Due to the slow electrode kinetics, the anodic peak of FLE on the bare electrode is very weak (Δi pa (FLE) = 0.2533 μA) and Δi pa ([Fe(CN)6] 3- ) is 0.01667μA. Δi on BPNS / GCE pa (FLE)(0.3080μA) and Δi pa ([Fe(CN)6] 3- )(0.05200μA) increased, which may be due to the improved electron transfer of BPNSs. When BPNS-Au / AgNP modified GCE, Δi pa (FLE) and Δi pa ([Fe(CN)6] 3- ) increased to 0.5997μA and 0.07167μA, respectively, which was mainly due to the improvement of the stability and electrocatalytic activity of BPNS by Au / AgNP functionalization. When the imprinted PPy film modified GCE, BPNS / GCE, and BPNS-Au / AgNP / GCE, their Δi pa (FLE) and Δi pa ([Fe(CN)6]3- ) increased significantly to 1.730μA / 0.07900μA, 2.172μA / 0.1277μA and 9.179μA / 1.170μA, which is mainly due to the strong adsorption capacity and specific recognition ability of the imprinted PPy membrane. pa (FLE) and Δi pa (Fe(III)) reached the maximum in MIP / BPNS-Au / AgNP / GCE, which was about 4 times that of MIP / GCE. pa ([Fe(CN)6] 3- ) is about 14 times that of MIP / GCE. pa (FLE) and Δi pa ([Fe(CN)6] 3- ) are both small (Δi pa (FLE) = 0.705 μA; Δi pa ([Fe(CN)6] 3- )=0.05067μA), which is significantly lower than that of MIP / BPNS-Au / AgNP / GCE. This may be due to the poor conductivity and lack of imprinting sites on the NIP membrane, which seriously hinders the electron transfer.
[0114] 3.3 Electrochemical oxidation mechanism of FLE
[0115] To elucidate the electrochemical oxidation mechanism of FLE in MIP / BPNS-Au / AgNP / GCE, after incubation in 10 μM FLE, the samples were electrochemically charged at different voltages (20–220 mV s -1 )Record the CV curve of FLE ( Figure 7 A). As v increases, the anodic peak of FLE shifts positively and the peak current increases gradually. In addition, no obvious cathodic peak appears in the reverse scan, indicating that the redox reaction of FLE on MIP / BPNS-Au / AgNP / GCE is irreversible. Figure 7 As shown in B, the peak current of FLE is highly correlated with v (i pa (μA)=0.1449v(mV s -1 )+0.01156,R 2 =0.9999), and i pa The double logarithmic plot of v approximates a straight line ( Figure 7 C), the slope is 1.001, indicating that FLE oxidation is controlled by adsorption. pa As lnv increases linearly ( Figure 7 D), the linear regression equation is E pa (V) = 0.03842ln(v / mV s-1 )+0.7855,R 2 =0.9935. For irreversible electrochemical reactions, the charge transfer coefficient (α) is generally assumed to be 0.5. Combined with the Laviron equation, the number of electrons transferred during FLE oxidation (n) is approximately 1. As described in Section 4.3.2, the number of protons and electrons involved in FLE electrochemical oxidation is equal. Therefore, it is speculated that FLE oxidation involves 1 electron and 1 proton. The possible FLE oxidation mechanism of MIP / BPNS-Au / AgNP / GCE is as follows: Figure 7 As shown in E.
[0116] 3.4 Linear response range and detection limit
[0117] Δi on MIP / BPNS-Au / AgNP / GCE in different concentrations of FLE or VA recorded by LSV under optimal conditions pa (FLE) and Δi pa ([Fe(CN)6] 3- ) quantitative analysis of the content of FLE and VA. Figure 8 As shown in A and 8B, Δi pa ([Fe(CN)6] 3- ) decreased with the increase of VA concentration, and the standard curves at 0.001–1.0 μM and 1.0–10 μM were i pa (μA)=0.3172C(μM)-0.6777(R 2 =0.9901) and i pa (μA)=0.05108C(μM)-0.9441(R 2 =0.9898), the linear detection range was 0.001–10 μM, and the LOD (3σ / S, where σ is the standard deviation of 7 consecutive blank tests and S is the slope of the standard curve at a lower concentration) was 0.17 nM. pa (FLE) gradually increases, while Δi pa (Fe(III)) was significantly reduced ( Figure 8 C). In the range of 0.001-10 μM, Δi pa ([Fe(CN)6] 3- ) is linearly related to FLE concentration ( Figure 8 D), whose standard curve is i pa (μA)=0.1144C(μM)-0.5347(R 2 =0.9901); i pa (FLE) also showed a linear correlation with the concentration of FLE in the range of 0.001-10 μM ( Figure 8 E), whose standard curve is i pa(μA)=4.350C(μM)+1.416(R 2 =0.9984) and i pa (μA)=0.6697C(μM)+5.143(R 2 =0.9976). The LOD of FLE was 0.25 nM (S / N=3). These results indicate that MIP / BPNS-Au / AgNP / GCE can simultaneously detect the non-electroactive substance VA and the electroactive substance FLE.
[0118] 3.5 Anti-interference ability test
[0119] To confirm the anti-interference ability of MIP / BPNS-Au / AgNPs / GCE, Δi was recorded after incubation with 1 μM FLE and VA structural analogs or potential interferents present in actual samples. pa (FLE) and Δi pa ([Fe(CN)6] 3- ).like Fig. 9 The results showed that no obvious anodic peak was detected after incubation with 1 μM of each interferent. In order to further evaluate the anti-interference property of MIP / BPNS-Au / AgNP / GCE, Δi was also recorded in the presence of the same concentration of potential interferents. pa (FLE) and Δi pa ([Fe(CN)6] 3- ), and their relative errors were all less than 5%, indicating that FLE and VA preferentially bound to the imprinted cavity. These results confirmed that MIP / BPNS-Au / AgNP / GCE had strong anti-interference ability.
[0120] 3.6 Repeatability, reproducibility and stability test
[0121] For repeated use, after each test, the modified electrode was immersed in 0.1 M NaOH solution and subjected to 20 cycles of CV scanning (potential range: -1.0-+1.0 V; scanning rate: 100 mV s -1 ) to remove the bound dual template molecules VA and FLE. To verify the practicality of MIP / BPNS-Au / AgNP / GCE, the repeatability, reproducibility and stability were also evaluated ( Fig.10 ). The RSDs of 7 consecutive tests incubated in 1 μM FLE and VA solutions were 2.97% and 1.99%, respectively, indicating that MIP / BPNS-Au / AgNPs / GCE has good repeatability. The RSDs of 5 independent MIP / BPNS-Au / AgNPs / GCE parallel determinations of 1 μM FLE and VA were 4.89% and 2.98%, respectively, indicating that the electrode preparation has good reproducibility. In addition, after 28 days, the ipa They still maintained at 83.05% and 85.02% of the original values, respectively, confirming that MIP / BPNS-Au / AgNP / GCE has good stability.
[0122] 5) Actual sample measurement
[0123] MIP / BPNS-Au / AgNP / GCE was used for the quantitative determination of FLE and VA in actual samples. Skim pure milk (250 mL / bag, Yili) was purchased from a local supermarket. Pure milk samples were diluted 100 times with 0.1 M PBS (pH = 5). Sewage was taken from the pool in front of the library of Hunan University of Technology. Different concentrations of FLE and VA standard solutions were added to milk and sewage, respectively, and then the recovery rate was determined.
[0124] The detection results of FLE and VA in sewage and milk samples are shown in Tables 3 and 4, respectively.
[0125] Table 3
[0126]
[0127] Table 4
[0128]
[0129]
[0130] As can be seen from Tables 3 and 4, no FLE and VA residues were found in sewage and milk samples. After adding FLE and VA standard solutions with known concentrations, the recovery rate was 91.17-107.97%. The sensor was incubated with sewage and milk samples with different concentrations of FLE (0.1-1μM) and VA (0.1-1μM) and the electrochemical performance test results were linearly fitted. The results are shown in Figure 3. Fig.11 As shown in the figure, the electrochemical performance of MIP / BPNS-Au / AgNP / GCE after incubation in sewage and milk with different concentrations of FLE (0.1-1μM) and VA (0.1-1μM) is linear, and its slope is close to the standard curve, indicating that it can be well applied to the detection of actual samples.
[0131] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
Claims
1. A dual-template molecularly imprinted modified electrode based on black phosphorus-gold / silver nanocomposite material, characterized in that: The modified electrode comprises an electrode substrate, on which an electrode sensitizing material layer and a dual-template molecular imprinting polymer film layer are sequentially modified, wherein an electrochemical probe is combined in the dual-template molecular imprinting polymer film layer, wherein the electrode sensitizing material layer comprises a black phosphorus nanoparticle-gold / silver nanoparticle composite material, and the template of the dual-template molecular imprinting polymer film layer is fleroxacin and vancomycin.
2. The dual-template molecularly imprinted modified electrode based on black phosphorus-gold / silver nanocomposite material according to claim 1, characterized in that: The electrochemical probe contains methylene blue, ferrocene or [Fe(CN)6] 3- / 4- Any one of the following; and / or, the electrode substrate is at least one of a glassy carbon electrode, a screen-printed carbon electrode, and a gold electrode; and / or, the polymer film layer is at least one of a polypyrrole film layer, a polyaniline film layer, a polythiophene film layer, a polydopamine film layer, and a poly-o-phenylenediamine film layer.
3. The method for preparing a dual-template molecularly imprinted modified electrode based on black phosphorus-gold / silver nanocomposite material according to claim 1 or 2, characterized in that: The steps include: S1. Preparing a black phosphorus nanoparticle-gold / silver nanoparticle composite material: mixing chloroauric acid and black phosphorus, reacting them under ultraviolet light, collecting a solid phase part I by solid-liquid separation, preparing the solid phase part I into a dispersion liquid I, adding a silver salt, dispersing the silver salt in the dispersion liquid I, reacting them again under ultraviolet light, and collecting a solid phase part II by solid-liquid separation again, thereby obtaining a black phosphorus nanoparticle-gold / silver nanoparticle composite material; S2, preparing the black phosphorus nanoparticle-gold / silver nanoparticle composite material into a dispersion II, so that the dispersion forms an electrode sensitization material layer on the electrode substrate; S3, forming a double-template molecular imprinting polymer film layer by electropolymerizing the functional monomers and the template molecules on the surface of the electrode sensitizing material layer; S4, eluting and removing the template, placing in an electrochemical probe solution so that the surface of the dual-template molecularly imprinted polymer film layer is bound to the electrochemical probe, thereby obtaining the modified electrode; Wherein, the template molecule is a mixture of fleroxacin and vancomycin.
4. The preparation method according to claim 3, characterized in that: The preparation method further comprises at least one of the following conditions: 1) In step S1, the molar ratio of chloroauric acid to silver salt is 0.5 to 2:1; and / or the molar ratio of black phosphorus to chloroauric acid is 10:15 to 25; 2) In step S3, the molar ratio of pyrrole, fleroxacin and vancomycin is 0.25-4:1:1; 3) The number of electropolymerization turns is 5 to 15 turns; 4) The template is eluted by electrochemical elution; the number of CV cycles in the elution process of the double template is more than 60 cycles through cyclic voltammetry scanning.
5. A dual-template molecular imprinting sensor based on black phosphorus-gold / silver nanocomposite material, characterized in that: The sensor comprises an electrode system and a supporting electrolyte solution, wherein the electrode system comprises the modified electrode as claimed in claim 1 or 2.
6. A method for preparing a dual-template molecular imprinting sensor based on black phosphorus-gold / silver nanocomposite material, characterized in that: The method comprises the step of preparing the modified electrode by the preparation method as claimed in claim 3 or 4.
7. The preparation method according to claim 6, characterized in that: The preparation method also includes the step of taking an auxiliary electrode, a reference electrode and a supporting electrolyte solution to form a sensor, wherein the supporting electrolyte includes a phosphate buffer salt, the concentration of the phosphate buffer salt in the supporting electrolyte solution is 0.08 to 0.12 mol / L, and the pH of the supporting electrolyte solution is 4 to 7.
8. Use of the dual-template molecular imprinting sensor based on black phosphorus-gold / silver nanocomposite material as claimed in claim 5 in detecting FLE and / or VA.
9. A method for detecting antibiotics using the dual-template molecular imprinting sensor based on black phosphorus-gold / silver nanocomposite material as claimed in claim 5, characterized in that: The method comprises the following steps: placing the modified electrode in a solution containing a supporting electrolyte and an antibiotic, adopting a dual signal strategy, and using [Fe(CN)6] 3- / 4- The electrochemical probe is used to detect the antibiotics by voltammetry; wherein the antibiotics include fleroxacin and / or vancomycin, and the voltammetry is one of linear sweep voltammetry, differential pulse voltammetry, and square wave pulse voltammetry.
10. The method according to claim 9, characterized in that: The incubation time is 6 to 10 minutes.
Citation Information
Patent Citations
Preparation method of glyphosate molecularly-imprinted electrochemical sensor
CN106226370A
Electrochemical luminescence aptamer sensor for specifically detecting kanamycin as well as preparation method and application of electrochemical luminescence aptamer sensor
CN112505116A
Electrode, sensor and instant detection system for detecting drugs containing phosphonic acid groups
CN114813878A
A composition and fabrication of sensor material using molecular imprinted polymer layer for detection of volatiles
WO2024110997A1